Mechanisms of nanotoxicity – biomolecule coronas protect pathological fungi against nanoparticle-based eradication. Issue 9 (20th October 2020) - Stauber, Roland H.; Westmeier, Dana; Wandrey, Madita; Becker, Sven; Docter, Dominic; Ding, Guo-Bin; Thines, Eckhard; Knauer, Shirley K.; Siemer, Svenja
Abstract: Whereas nanotoxicity is intensely studied in mammalian systems, our knowledge of desired or unwanted nano-based effects for microbes is still limited. Fungal infections are global socio-economic health and agricultural problems, and current chemical antifungals may induce adverse side-effects in humans and ecosystems. Thus, nanoparticles are discussed as potential novel and sustainable antifungals via the desired nanotoxicity but often fail in practical applications. In our study, we found that nanoparticles' toxicity strongly depends on their binding to fungal spores, including the clinically relevant pathogen Aspergillus fumigatus as well as common plant pests, such as Botrytis cinerea or Penicillum expansum . Employing a selection of the model and antimicrobial nanoparticles, we found that nanoparticle-spore complex formation is influenced by the NM's physicochemical properties, such as size, identified as a key determinant for our silica model particles. Biomolecule coronas acquired in pathophysiologically and ecologically relevant environments, protected fungi against nanoparticle-induced toxicity as shown by employing antimicrobial ZnO, Ag, or CuO nanoparticles as well as dissolution-resistant quantum dots. Mechanistically, dose-dependent corona-mediated resistance was conferred via reducing the physical adsorption of nanoparticles to fungi. The inhibitory effect of biomolecules on nano-based toxicity of Ag NPs was further verified in vivo, using the invertebrate Galleria mellonella as an alternative non-mammalian infection model. We provide the first evidence that biomolecule coronas are not only relevant in mammalian systems but also for nanomaterial designs as future antifungals for human health, biotechnology, and agriculture.